A PROSPECTIVE STUDY OF COMPARING PERIOPERATIVE HEMODYNAMIC AND ANALGESIC EFFECTS OF COMBINATION OF DEXMEDETOMIDINE AND ROPIVACAINE WITH PLAIN ROPIVACAINE IN USG GUIDED INTERSCALENE BRACHIAL PLEXUS BLOCK FOR ELECTIVE SHOULDER ARTHROSCOPIC SURGERIES. - Dr. Aaqib Hassan; Dr. Shabir Ahmad Shabir; Dr. Ch Abdul Rahoof; Dr. Hinna Bashir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
BackgroundAbstract: Peripheral nerve blocks are frequently used as an alternative or adjuvant to general anesthesia and as a means of attenuating postoperative pain.Aim: To observe and compare the effects of Dexmedetomidine and Ropivacaine combination with Ropivacaine alone on perioperative hemodynamic parameters and postoperative analgesia. Methods:  The present observational study was conducted in Bone and Joint Hospital, an associated hospital of Government Medical College, Srinagar from February 2020 to October 2021. 50 patients were observed in the study who underwent interscalene brachial plexus block for shoulder arthroscopic surgery 30 minutes before general anaesthesia. Patients were equally divided into two groups of 25 patients each using a computer generated sequence of random numbers in 1:1 ratio.  Hemodynamic parameters such as heart rate (bpm), systolic blood pressure (mmHg), diastolic blood pressure (mmHg), mean arterial pressure (mmHg) and SpO2 (%) were monitored postoperatively upto 24hours. Patient’s pain score was assessed using VAS (0–10)86. Patient’s pain score using VAS was recorded every 3 hrs for 24 hours. Time for first rescue analgesic given and number of doses of rescue analgesics given were also recorded. Patient’s satisfaction was assessed using Likert Satisfaction Scale. Side effects in the form of nausea, vomiting, hypotension, bradycardia and hypoxemia were recorded.Results: Comparison of haemodynamic parameters among two study groups was found to be statistically significant at all-time intervals except baseline, but the difference were within safety limits. Statistically significant difference was obtained when postoperative haemodynamic parameters were compared among two study groups but the difference was within safety limits. Duration of analgesia was high in Group 1 (dexmedetomidine + ropivacaine) compared to Group 2 (ropivacaine alone). Time of request for rescue analgesia was higher in Group 1 group as compared to Group 2. Analgesia was better and statistically significant at 6 hours, 9 hours, 12 hours, 15 hours and 21 hours (p < 0.05) postoperatively in Group 1 compared to Group 2. At all other time intervals the difference observed was statistically insignificant.Conclusion: We conclude that preoperative inter-scalene block given by adding dexmedetomidine to ropivacaine reduces the analgesic requirement intraoperatively as well postoperatively with favorable hemodynamic changes.